Determinantes locais da decomposição foliar e de raízes finas em um ecossistema semiárido do nordeste brasileiro - Costa, Uirande Oliveira (2012)
The decomposition process exercises an extensive control over the carbon cycle, affecting its availability and nutrient cycling in terrestrial ecosystems. The understanding of leaf decomposition patterns above the soil and fine roots decomposition below the soil is necessary and essential to identify and quantify more accurately the flow of energy and matter in forest systems. There is still a lack of studies and a large gap in the knowledge about what environmental variables act as local determinants over decomposition drivers. The knowledge about the decomposition process is still immature for Brazilian semiarid region. The aim of this study was to analyze the decomposition process (on leaves and fine roots) of a mixture of three native species for 12 months in a semiarid ecosystem in Northeast Brazil. We also examined whether the rate of decomposition can be explained by local environmental factors, specifically plant species richness, plant density and biomass, soil macro-arthropods species richness and abundance, amount of litterfall and fine root stock. Thirty sampling points were randomly distributed within an area of 2000 m x 500 m. To determine the decomposition rate, the litterbag technique was used and the data analysis were made with multiple regressions. There was a high degradation of dead organic matter along the experiment. Above ground plant biomass was the only environmental local factor significantly related to leaf decomposition. The density of vegetation and litter production were positively and negatively related to decay rates of fine roots, respectively. The results suggest that Caatinga spatial heterogeneity may exert strong influences over the decomposition process, taking into account the action of environmental factors related to organic matter exposure of and the consequent action of solar radiation as the decomposition process main controller in this region